2013
DOI: 10.1189/jlb.1112584
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of TCR/CD3 complex CD3ɛ chains of regulatory CD4+ T (Treg) lymphocytes: role in Treg differentiation in vitro and impact on Treg in vivo

Abstract: Tregs are anergic CD4(+)CD25(+)Foxp3(+) T lymphocytes exerting active suppression to control immune and autoimmune responses. However, the factors in TCR recognition underlying Treg differentiation are unclear. Based on our previous data, we hypothesized that Treg TCR/CD3 antigen receptor complexes might differ from those of CD4(+)CD25(-) Tconv. Expression levels of TCR/CD3, CD3ε,ζ chains, or other molecules involved in antigen signaling and the characteristics of CD3ε chains were analyzed in thymus or spleen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 86 publications
(103 reference statements)
2
18
0
Order By: Relevance
“…Notably, the same group reported that CD4 + Foxp3 + T cells isolated from C57BL/6 mice have more undegraded CD3ε and less N-terminal-degraded CD3ε isoforms than do CD4 + Foxp3 2 T cells. This feature accounts for the difference in the avidity to two anti-CD3 (namely, the YCD3-1 and 500A2 clones) (17,35). However, neither of the previously cited studies demonstrated either the ability of nonmitogenic tolerogenic anti-CD3 (i.e., the 145-2C11 clone used in our study) to discriminate the two different isoforms, or the expression of differing CD3ε isoforms in T cells from NOD mice (17,35).…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Notably, the same group reported that CD4 + Foxp3 + T cells isolated from C57BL/6 mice have more undegraded CD3ε and less N-terminal-degraded CD3ε isoforms than do CD4 + Foxp3 2 T cells. This feature accounts for the difference in the avidity to two anti-CD3 (namely, the YCD3-1 and 500A2 clones) (17,35). However, neither of the previously cited studies demonstrated either the ability of nonmitogenic tolerogenic anti-CD3 (i.e., the 145-2C11 clone used in our study) to discriminate the two different isoforms, or the expression of differing CD3ε isoforms in T cells from NOD mice (17,35).…”
Section: Discussionmentioning
confidence: 40%
“…During the last 10 y, Lambert and Genin (15) and El Hentati et al (16) (17). The present study sought to: 1) define, by means of unsupervised analysis of flow cytometry data, whether CD3 heterogeneous expression levels occur in T cell subsets isolated from mice and humans; and 2) evaluate the biological impact of CD3 expression heterogeneity on anti-CD3 treatment in vivo.…”
Section: Foxp3mentioning
confidence: 99%
“…Consequently, their proportion increased in both lymphoid organs and the transplanted islets at the end of treatment. The molecular mechanisms underlying such Treg resistance to apoptosis are not fully understood, but may include a reduced expression and activation of signaling molecules downstream of the TCR/CD3 complex as well as a decreased expression of the CD3 molecules at the cell surface compared to CD4 + Foxp3 − T lymphocytes (2123). …”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the differential impact of anti-CD3 mAbs may be due to low-level expression of CD3 in CD4 + CD25 + T cells compared to CD4 + CD25 - T cells [30]. Other authors reported that the TCR signalling is attenuated in Foxp3-expressing cells, possibly due to impaired TCR-mediated activation of the Akt pathway [31].…”
Section: Discussionmentioning
confidence: 99%